A Review of Illegal, Unreported and Unregulated (IUU) Fishing: Global Trends, Drivers, Impacts and Management Responses - Adagha, O.; Evugbomore, P. (Journal of Science Research and Reviews, 2026)
Fish and other aquatic resources are critical to global food security, economic development, and livelihoods, especially in developing countries. However, illegal, unreported, and unregulated (IUU) fishing continues to jeopardise fisheries’ viability and undercut global conservation and management efforts. This article investigates the idea and forms of IUU fishing, identifies the primary causes, and assesses the environmental, economic, and social consequences. It also examines current management and policy responses on the national and international levels. Furthermore, the study identifies rising global trends in IUU fishing, such as its concentration in weakly governed countries like West Africa and the growing sophistication of illegal fishing operations. The study highlights the importance of stronger governance frameworks, better monitoring and enforcement systems, improved traceability in seafood supply chains, and expanded international cooperation. Strengthening these measures is crucial for ensuring sustainable fisheries management and protecting marine biodiversity.